KENDALA PERUBAHAN STATUS BADAN KREDIT DESA MENJADI LEMBAGA KEUANGAN MIKRO DITINJAU DARI UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - A. Zaky Fuad; Risma Nur Arifah (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2020)
POJK Number 10/POJK.03/2016 about fulfilment rules Credit Bank of People and transformation, BKD to commit a process of Credit Bank of People explain that BKD (Village Credit Agency) an effort reinforcement institutions that have legal entities. In practice, this transformation is not easy, a recurring obstacle among others accordance asset ownership status. This research is study of empirical law with with a socilogical juridical approach, a concept approach, and a legislation approach. The results showed that the constraints of status changes that occurred in BUMDES in Genteng Subdistrict has several factors, including unclear regulations punlished by the government related to the mechanisms of transforming BKD into BUMDES, management of Human Resources (HR) which was not maximized, lack of response and support from the community. While efforts to resolve the status change constraints include the village government giving concrete understanding of the community related to changing the status of the BKD into BUMDES, uniting the vision and mission of the organizer, holding a discussion forum with several layers related and involved in the process of transferring status. While efforts to resolve constraint by Islamic law with holding a consensus deliberation for common wealth which in the end BKD in Banyuwangi Regency agreed to do cooperation between BUMDES which in this case BUMDES together trough PT. BKD Banyuwangi in order to save assets.